Interconnected 3D carbon network with enhanced reaction kinetics and architecture stability for advanced potassium-ion hybrid capacitors. Issue 5 (25th January 2022) - Yuan, Fei; Zhang, Di; Yu, Qiyao; Li, Zhaojin; Wang, Qiujun; Wang, Huan; Wu, Yusheng; Wang, Bo
Abstract : N-doped amorphous porous carbon (marked as NPC) is synthesized. The resulting NPC has improved reaction kinetics and structure stability, and thus exhibits ultra-long cycling life, high-energy density, and power density. Abstract : Due to their high energy/power densities and ultralong cycle lifespan, potassium-ion hybrid capacitors (PIHCs) have attracted increasing research interest for large-scale energy storage systems. However, the kinetics mismatch between the battery-type anodes and capacitor-type cathodes severely hampers the further development of PIHCs. Herein, the kinetics-enhanced N-doped amorphous porous carbon with an interconnected three-dimensional (3D) network (marked as NPC) is reported. The existence of an amorphous configuration can provide numerous storage potassium sites, while the interconnected 3D network contributes to electron transfer, thus improving the reversible capacity and reaction kinetics of NPC. The expanded carbon interlayer spacing, well-established porous structure and plentiful active sites induced by N-doping greatly boost the structural stability and further increase kinetics. Benefiting from these structure merits, the NPC electrode delivers a high capacity (257.7 mA h g −1 at 0.5 A g −1 ), an excellent rate capability (199.5 mA h g −1 at 2 A g −1 ), and an extraordinary cycling stability over 3000 cycles at 2 A g −1 . Moreover, coupling with activated carbon (AC) cathode and NPC anode, the assembled PIHCs exhibit ultra-large energy/ultra-high power density (177.3 W h kg −1 and 19348.3 W kg −1 ) with a long cycling life (81.6% capacity retention after 3000 cycles).